2014
DOI: 10.18632/oncotarget.2388
|View full text |Cite
|
Sign up to set email alerts
|

NEK2 mediates ALDH1A1-dependent drug resistance in multiple myeloma

Abstract: We reported previously that increased expression of aldehyde dehydrogenase 1 (ALDH1) in multiple myeloma (MM) is a marker of tumor-initiating cells (TICs) that is further associated with chromosomal instability (CIN). Here we demonstrate that member A1 of the ALDH1 family of proteins, ALDH1A1, is most abundantly expressed in myeloma. Enforced expression of ALDH1A1 in myeloma cells led to increased clonogenicity, tumor formation in mice, and resistance to myeloma drugs in vitro and in vivo. The mechanism underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…58 Finally, NEK2 regulates centrosome disjunction/splitting and is highly correlated with drug resistance, rapid relapse, and poor outcome in MM and many other cancers. 47,59 All these data indicate that activity of the APRIL/BCMA pathway plays a central role in MM pathogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…58 Finally, NEK2 regulates centrosome disjunction/splitting and is highly correlated with drug resistance, rapid relapse, and poor outcome in MM and many other cancers. 47,59 All these data indicate that activity of the APRIL/BCMA pathway plays a central role in MM pathogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Clonogenic growth was performed as previous reported (25). Briefly, 10,000 myeloma cells were plated in 0.5 mL 0.33% agar/RPMI 1640 (Invitrogen) supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 29 of 285 genes that were associated with MM were located in chr 9 [23-31]. Gene gain and loss in chr 9 were analyzed and compared according to drug response, and it was observed that KMS-12-BM, which is resistant to BTZ, showed an increase of CNAs after BTZ treatment (Table 3).…”
Section: Resultsmentioning
confidence: 99%